WAYS TO ATTRACT ADDITIONAL INVESTMENTS IN THE ECONOMY OF UKRAINE - Boreiko , V.I. (The actual problems of regional economy development, 2016)
In the article investigated the role of investment resources in ensuring the dynamic development of the economy of countries; analyzed the dynamics earnings of direct foreign investments in Ukraine and deposits of the population attracted by commercial banks; proved that to create a favorable environment for investors, Ukraine should strengthen legal protection of the commercial interests of investors and provide them with tax breaks, provide insurance their of industrial and commercial risks, cancel taxation of deposits of citizens and to reimburse them the full amount of deposits in bankruptcy of commercial banks. JEL: O 16